The Impact of Exchange Rate on Poland's Trade Flows - Katarzyna Twarowska (International School for Social and Business Studies, 2015)
The aim of this paper is to investigate the effect of exchange rate on Poland's foreign trade, especially on bilateral trade flows between Poland and the Euro area, which is its major trading partner. The research verifies the theoretical concepts that explain how the exchange rate influences the trade turnover. The empirical analysis was preceded by a theoretical basis of the problem. Data used in this study covers the period from 2004 to 2013. The theoretical and empirical analysis confirm that the exchange rate is a substantial factor influencing bilateral trade turnover between Poland and its main trading partners. The Polish zloty depreciation is the cause for the Polish exports growth. In the case of imports, the depreciation of the Polish zloty causes a decrease of the value of the Polish imports. Moreover, the exchange rate is an important adjustment mechanism, thanks to which the Polish economy was able to avoid a large decline in exports and GDP during the recent financial and economic crisis.